Between a Rock and a Hard Place: Afghan Migration to Europe From Iran - Crawley, Heaven (2022)
Afghans have consistently been one of the largest groups of refugees arriving in Europe, with more than 600,000 Afghan asylum applications in European countries over the past ten years, second only in number to Syrians. Afghan migration to Europe is a response to both the deteriorating security situation in Afghanistan and protracted displacement in countries hosting the vast majority of Afghan refugees, including Iran, where there is a well‐documented lack of protection, rights, and opportunities. Drawing on interviews undertaken in Turkey and Greece during the last three months of 2015, this article examines the experiences of Afghans who travelled to Europe from Iran, where they had been living for many years, and in some cases had been born. Their experiences, particularly when seen in the context of Afghan mobility historically, complicate dichotomies between “forced” and “voluntary” migration, and “origin” and “destination” countries, which underpin the Common European Asylum System. It is clear that mobility forms an important survival strategy for Afghans and others living in situations of protracted displacement, for whom efforts to provide durable solutions have been largely unsuccessful. Harnessing this mobility by facilitating and supporting—rather than preventing—onward migration is the key to unlocking protracted displacement.